THE INFLUENCE OF BRAND AWARENESS, PERCEIVED QUALITY, AND BRAND ASSOCIATION ON BRAND LOYALTY: A STUDY OF CUSTOMERS PT. GOJEK INDONESIA IN JAKARTA - Rizky Akbar Handriono (Jurnal Ilmiah Mahasiswa FEB, 2016)
The  purpose  of  this  research  is  to  examine  the  influence  of  Brand  Awareness, Perceived Quality, and Brand Association on Brand Loyalty of Customers PT. Gojek Indonesia in Jakarta both partially and simultaneously. Further purposive sampling technique was used in this research 100 respondents. The analysis tools are Multiple Linear Regression Analysis to determine the relationship between independent variable and dependent variable. The result of this research shows that there is a significant effect simultaneously and partially between Brand Awareness, Perceived Quality, and Brand Association on Brand Loyalty. While Brand Association is the most dominant variable that effect on Brand Loyalty.Keywords: Brand Awareness, Perceived Quality, Brand Association, Brand Loyalty